2005
DOI: 10.1007/s00402-005-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Segmental fracture of the scaphoid: report of a rare fracture pattern

Abstract: Scaphoid fracture patterns are generally consistent and predictable, occurring most commonly through the waist of the bone. Mechanism for injury is thought to be hyperextension of the wrist. Comminution, with or without a butterfly fragment, is occasionally seen, as are simultaneous tuberosity fractures. We suggest that the mechanism in this case may have been multiple or secondary trauma, or an effect of loaded rotation. We highlight the need for careful imaging of the scaphoid bone prior to choosing treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the case by da Assunção et al , the fracture pattern was identified as segmental only intraoperatively 31. The fracture was fixed with a single Herbert screw and union was achieved 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In the case by da Assunção et al , the fracture pattern was identified as segmental only intraoperatively 31. The fracture was fixed with a single Herbert screw and union was achieved 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Scaphoid fractures are relatively common, while comminuted and segmental fractures are less commonly reported [1][2][3]. Furthermore, to the best of our knowledge, there are no reports in the literature of an open comminuted scaphoid fracture dislocation.…”
Section: Introductionmentioning
confidence: 99%